Dextromethorphan/quinidine sulfate (Zenvia) for Pseudobulbar Affect - Rosen, Howard (2008)
A new agent containing a combination of Dextromethorphan and Quinidine is currently under development for the treatment of pseudobulbar affect (PBA). PBA is a disorder of emotional regulation, characterized by uncontrollable outbursts of laughing and/or crying that are disproportionate to the emotions being experienced. The pathophysiology of PBA is currently unknown, although the disorder is thought to occur exclusively in the setting of neurological disease. The most influential theory on PBA posits that emotional outbursts are being generated in the brainstem autonomously due to loss of regulatory control by the frontal lobes. Although rarely life-threatening, PBA can have significant impact on patients’ quality of life and thus merits treatment. There are currently no approved treatments for PBA. Several agents have been found to be effective in small placebo-controlled trials and case series, with the most commonly used agents being tricyclic antidepressants and selective serotonin reuptake inhibitors. Both these treatments are inexpensive and relatively low-risk, although the quality and quantity of the available data on their efficacy are not optimal. DM has several pharmacological mechanisms of action relevant to the brain. It is an NMDA-receptor antagonist, which prompted investigators to study its potential for slowing progression in ALS, where glutamate toxicity is thought to be a factor. The combination agent DM/Q was developed to slow the metabolism of DM by P450 2D6 enzymes in the liver. DM/Q was not effective in slowing ALS progression, but patients noted that it helped to control their emotional outbursts, suggesting it might be useful as a treatment for PBA. DM is also a sigma1 receptor agonist. These receptors are widely distributed in the brain, but probably most heavily in the limbic system, suggesting that DM may exert its emotion-controlling effects via these receptors. The endogenous ligands for sigma1 receptors are not altogether known, although they appear to include gonadal steroids. DM/Q was recently shown to be effective in reducing the severity of PBA in two large studies of Amyotrophic Lateral Sclerosis (ALS) and Multiple Sclerosis (MS), which are probably the most common neurological settings. These are the largest treatment studies of PBA ever done. The agent was safe and relatively well tolerated. Further studies are being conducted to see if efficacy can be maintained with lower doses of quinidine. If DM/Q is approved by the FDA for treatment of PBA, this would be the first agent approved for this purpose. Currently, the antidepressants are probably the most attractive pharmacologic options for treatment of PBA. The choice of whether to use DM/Q in this setting will likely depend on individual patient factors, as well as cost.